Rebound of Hepatitis B Virus Replication in HepG2 Cells after Cessation of Antiviral Treatment - Abdelhamed, Ayman M. (American Society for Microbiology, 2002)
Treatment of patients with lamivudine (3TC) results in loss of detectable levels of hepatitis B virus (HBV) DNA from serum; however, the relapse rate, with regard to both reappearance of virus in the bloodstream and hepatic inflammation, is high when therapy is terminated. Although the rebound observed in patients has also been seen in animal hepadnavirus models, rebound has not been analyzed in an in vitro cell culture system. In this study, we used the HBV recombinant baculovirus/HepG2 system to measure the time course of antiviral agent-mediated loss of HBV replication as well as the time course and magnitude of HBV production after release from antiviral treatment. Because of the sensitivity of the system, it was possible to measure secreted virions, intracellular replicative intermediates, and nuclear non-protein-bound HBV DNA and separately analyze individual species of DNA, such as single-stranded HBV DNA compared to the double-stranded form and relaxed circular compared to covalently closed circular HBV DNA. We first determined that HBV replication in the HBV recombinant baculovirus/HepG2 system could proceed for at least 35 days, with a 30-day plateau level of replication, making it possible to study antiviral agent-mediated loss of HBV followed by rebound after cessation of drug treatment. All HBV DNA species decreased in a time-dependent fashion following antiviral treatment, but the magnitude of decline differed for each HBV DNA species, with the covalently closed circular form of HBV DNA being the most resistant to drug therapy. When drug treatment ceased, HBV DNA species reappeared with a pattern that recapitulated the initiation of replication, but with a different time course.